Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4103/2249-4863.154653
|View full text |Cite
|
Sign up to set email alerts
|

How healthy is our geriatric population? a community-based cross-sectional study

Abstract: Introduction:With the rise in aged population there is a greater need to look into their nutritional and physical disability aspects which is otherwise neglected. The study aimed to assess the prevalence of malnutrition, anemia and physical disability among the community-dwelling aged population.Materials and Methods:A cross-sectional study was carried out in a rural block of north Tamil Nadu. Seventeen villages were selected using cluster sampling based on probability proportional to size. A total of 340 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 12 publications
(13 reference statements)
3
23
0
Order By: Relevance
“…A significant association was found between low MNA scoring and advanced age. 8,12,13 A study conducted by Reddy et al in rural areas of Tamil Nadu observed that the mean age of the entire study population was 69.8±7.8 years which was almost similar to our study. 14 In the present study, 55% of the participants were females with female to male ratio of 1.25:1 suggesting female predominance.…”
Section: Discussionsupporting
confidence: 89%
“…A significant association was found between low MNA scoring and advanced age. 8,12,13 A study conducted by Reddy et al in rural areas of Tamil Nadu observed that the mean age of the entire study population was 69.8±7.8 years which was almost similar to our study. 14 In the present study, 55% of the participants were females with female to male ratio of 1.25:1 suggesting female predominance.…”
Section: Discussionsupporting
confidence: 89%
“…These may be compounded by physical incapacity due to an exhaustive list of disabilities because of multiple medical problems of varying severity. [3][4][5][6][7][8][9][10][11][12][13] The cumulative effect of these may be much greater than any individual disease. The elderly who are living alone are likely to suffer more from both acute and chronic illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…A significant association was also found between low MNA scoring and advanced age in the study conducted by Patil et al 10 Study conducted by Paul et al, Agarwal et al and Krithika et al also showed similar association between advanced age and low MNA score. [11][12][13] The association between the female gender and nutritional status was found to be significant in our study. Similar findings were observed in the study conducted by Rashmi Agarwalla et al 11 Studies done by Saeidlou et al, Donini et al and Boulos et al also found similar results.…”
Section: Discussionmentioning
confidence: 58%